POLA KONSUMSI DALAM PERILAKU BERBELANJA PNS DOSEN DI IAIN PALU DALAM PANDANGAN EKONOMI ISLAM - Ermawati Usman (ISTIQRA, 2015)
Shopping is an activity of fulfillment. The percentage is dependent on the consumption patterns of a person. A consumption pattern is the percentage of the income distribution of each expenditure for food, clothing, services, recreation, and entertainment. Factors affecting consumption patterns, namely income, education, the prices of goods, environmental and consumer tastes. The imbalance in consumption patterns can influence shopping behavior. This study aimed to determine the consumption pattern in shopping behavior of IAIN Palu lecturer in the perspective of Islamic economics. This study used qualitative methods. The population in this study is all lecturers IAIN Palu, with a sample of 55 respondents. Sample selection is done with purposive sampling. The results showed that consumption patterns in shopping behavior of IAIN Palu lecturer influenced by level of education, income and prices of goods. Patterns are not well ordered is not the making of a shopping list before shopping to buy a non-priority item. Based on a review of Islamic economics lecturer consumption patterns of IAIN Palu not wasteful and prioritizing the benefit/maslahah goods in fulfillment